The Effect of Total Knee Arthroplasty on Physical Activity and Body Mass Index: An Analysis of the Osteoarthritis Initiative Cohort. (14th January 2019) - Rezzadeh, Kevin; Behery, Omar A.; Kester, Benjamin S.; Long, William J.; Schwarzkopf, Ran
Introduction: Preliminary analysis of accelerometry measurements has shown physical activity may not increase significantly after total knee arthroplasty (TKA). This study evaluates the effect of TKA on physical activity accelerometry measurements and body mass index (BMI). Methods: Using the multicenter Osteoarthritis Initiative (OAI) database, a cohort of patients with physical activity level accelerometry measurements and BMI before and after TKA was identified. Physical activity levels and BMI were acquired at pre-TKA and post-TKA accelerometry visits 2 years apart. Survey scores pertaining to knee functionality and quality of life were also analyzed before and after knee surgery. Each patient included in the study had a unilateral TKA completed between these 2 accelerometry visits. Accelerometry measurements, BMI of the patients, and survey scores relating to knee functionality and pain relief from before and after TKA were compared using paired samples t tests. Results: Twenty-three patients from the OAI database were identified for the paired analysis. They were evaluated at a mean postoperative follow-up of 15 months. There were no statistically significant differences between the post-TKA group and pre-TKA group for the accelerometry variables and BMI, though patients experienced a significant improvement in knee function and pain relief measures included in this analysis. Discussion: Although TKA can successfully restore function and relieve pain, there remains no good evidence that neither physical activity nor BMI improve postoperatively. Conclusion: No significant differences in physical activity and BMI were observed after TKA in this study.